Immunoadjuvant Prednisolone Therapy for HIV-Associated Tuberculosis: A Phase 2 Clinical Trial in Uganda - Mayanja-Kizza, Harriet; Jones-Lopez, Edward; Okwera, Alphonse; Wallis, Robert S.; Mugerwa, Roy D.; Uganda–Case Western Research Collaboration (The Journal of infectious diseases, 2005)
Human immunodeficiency virus (HIV)–infected patients with tuberculosis (TB) respond to effective antituberculous therapy, but their prognosis remains poor. Mounting evidence from clinical studies supports the concept of copathogenesis in which immune activation that is triggered by TB and mediated by cytokines stimulates viral replication and worsens HIV infection, especially when immune function is preserved. We performed a phase 2, randomized, double-blind, placebo-controlled clinical trial in Kampala, Uganda, to determine whether immunoadjuvant prednisolone therapy in HIV-infected patients with TB who have CD4+ T cell counts ⩾200 cells/μL is safe and effective at increasing CD4+ T cell countsShort-term prednisolone therapy reduced levels of immune activation and tended to produce higher CD4+ T cell counts. Although prednisolone therapy was associated with a more rapid clearance of Mycobacterium tuberculosis from the sputum, it was also associated with a transient increase in HIV RNA levels, which receded when prednisolone therapy was discontinued. The intervention worsened underlying hypertension and caused fluid retention and hyperglycemiaThe benefits of prednisolone therapy on immune activation and CD4+ T cell counts do not outweigh the risks of adverse events in HIV-infected patients with TB and preserved immune function
Keywords: cytokinehivhypertensionimmunologic adjuvantsprednisolonesputumt-lymphocytestuberculosisugandatuberculosis and hivblood hiv rnahiv infectionsadverse event